OCCUPATIONAL ACCIDENTS WITH BIOLOGICAL MATERIAL AMONG HEALTHCARE WORKERS - Manoel Carlos Arantes; Maria do Carmo Fernandez Lourenço Haddad; Sonia Silva Marcon; Mariana Angela Rossaneis; Paloma de Souza Cavalcante Pissinati; Samuel Andrade de Oliveira (Universidade Federal do Paraná, 2017)
The present study aimed at characterizing occupational accidents with biological material among healthcare workers. A retrospective, quantitative study of accidents involving biological material, conducted in a secondary reference hospital located in the northeastern region of the state of Paraná. Data were collected between December 2013 and June 2014 from 1,061 medical records of health professionals and registration sheets for the Notifiable Diseases Information System, and were analyzed using descriptive statistics. Among 1,061 occupational accidents with biological material, 58.1% occurred among nursing aides and technicians, of whom 82.7% were women. The main organic material present in 86.1% of the accidents was blood; 88.2% occurred through percutaneous exposure, 66.1% involved the use of needles with lumen, and 21.9% resulted from inappropriate disposal of sharps. It is necessary to implement preventive measures directed to the nursing team.